How secular and religiously free are Europe’s “secular” states? - Jonathan Fox (International Journal for Religious Freedom, 2023)
This study uses data from the Religion and State (RAS) project to examine the extent to which 43 European states are, in fact, secular and religiously free. I find that these European states engage in substantial levels of support for religion, regulation, restriction, and control (RRC) of the majority religion, and government-based discrimination (GRD) against religious minorities. This is true of both countries in Europe with official religions and those which declare separation of religion and state (SRAS) in their constitutions. This demonstrates a distinctly European pattern of state-religion relations that is influenced in no small part by anti-religious forms of secularism.